Counterterrorism strategies: successes and failures of six nations - Alexander, Yonah (Potomac Books, 2006)
Introduction -- United States / Yonah Alexander -- France / Guillaume Parmentier -- Germany / Ulrich Schneckener -- Italy / Sergio Marchisio and Germana Tappero Merlo -- Egypt / Ahmed Abou-el-Wafa -- Sri Lanka / Vernon L.B. Mendis -- Counterterrorism strategies : summary and conclusions / Yonah Alexander